Removing salt from rice paddies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A recent study visit by the leaders of the AgroBio AJAC/Kolda project (based in central Casamance, Senegal) to the famous Balante rice farmers of Guinea Bissau